2004
DOI: 10.1111/j.1542-474x.2004.94559.x
|View full text |Cite
|
Sign up to set email alerts
|

Beat‐to‐Beat Heart Rate and QT Variability in Patients with Congestive Cardiac Failure: Blunted Response to Orthostatic Challenge

Abstract: This impairment of postural changes of HR variability is most likely due to an impaired baroreceptor function in patients with congestive heart failure. The etiology of this is likely due to an increased cardiac sympathetic and a decreased vagal function. However, the relationship of postural changes in beat-to-beat QT interval variability and baroreflex need further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…However, this effect was absent in HF groups, strengthening the notion that sympathetic influences may only have limited influence on beat-to-beat repolarization stability in HF (8,19). As protracted sympathetic stimulation in chronic HF reduces the repolarization reserve (47), the autonomic status presumably ceases to notably affect QTV.…”
Section: Previous Studiesmentioning
confidence: 57%
“…However, this effect was absent in HF groups, strengthening the notion that sympathetic influences may only have limited influence on beat-to-beat repolarization stability in HF (8,19). As protracted sympathetic stimulation in chronic HF reduces the repolarization reserve (47), the autonomic status presumably ceases to notably affect QTV.…”
Section: Previous Studiesmentioning
confidence: 57%
“…9 A novel approach has been proposed to assess repolarization lability using the QT variability index (QTVi) to quantify beat-to-beat changes in the QT interval duration. 10 The QTVi is increased in CHF patients 11 and is a powerful predictor of arrhythmias and cardiac mortality. 10,12 In the present study, we evaluated QT variability in OSA patients and characterized the relationship between the severity of OSA and QT variability.…”
Section: Obstructive Sleep Apnea (Osa) Is a Common Dis-order Of Breatmentioning
confidence: 99%
“…QTd has been recognized as a significant prognostic, noninvasive marker of the inhomogeneity of myocardial repolarization in several diseases, especially those involving ischemic heart disease (Barr et al, 1994;Higham et al, 1995). An increase in QTd has been shown to correlate with an increased risk of arrhythmias in cardiac diseases and in congestive heart failure (Berger et al, 1997;Desai et al, 2004;Haigney et al, 2004). Consistent with those previous reports, we observed that QTd was elevated only in the 1-day ethanol withdrawal rats, who had shown the highest incidence of ventricular arrhythmic deaths in our previous study (Liu and Fujimiya, 2008, in which the same rat model was used).…”
Section: Discussionmentioning
confidence: 98%